PATIENT’S FACE COMPUTER-ASSISTED SIMULATION ON THE BASIS OF LATERAL-VIEW ORTHOGNATHIC MODELS - Y. D. Vasilyeva (Informatika)
Methods of predicting patient’s facial profile after malocclusion treatment are considered. Methods are based on the orthognathic models data base search for the profile, demonstrating the best patient’s face after the planned treatment. Practical application of these methods provides an opportunity to demonstrate the face after the planned treatment to the patient at the stage of preliminary diagnosis and can be useful for orthodontists in treatment planning and correction.